KINERJA MESIN DIESEL MENGGUNAKAN BAHAN BAKAR SOLAR, DME DAN CAMPURANNYA DENGAN SIMULASI DINAMIKA FLUIDA - Yuwono, Taufik; Rahardjo, Bambang Suwondo (Jurnal Energi dan Lingkungan (Enerlink), 2010)
Fuel atomization plays a main role in determining the performance of dieselengines, where the spray pattern illustrates fuel combustion occurs in thecombustion chamber. From fuel spray test results showed that fuel evaporationcharacteristics of fuel at a certain pressure will effect on engine performance.The higher the injection pressure will reduce the diameter of the fuel sprays(sauter mean diameter), thus speeding up evaporation and mixing processesbetween fuel and air in the combustion chamber with resulted the combustionprocess is more completely. Analysis of fuel atomization simulations performedat injection pressure 150, 180 and 235 bar on the distribution of size,temperature and concentration of air+fuel mixture. Physical chemical parametersresulting are the size and temperature distribution patterns fuel+air mixturesprays. DME is feasible to be used as alternative fuel in diesel engines by adding2?5% lubricant additives. The use of diesel+DME 50/50 mixed fuel provides thelowest fuel consumption by generating power of 3x2,975 watts.Kata kunci: kinerja mesin, solar, DME, simulasi atomisasi, dinamika fluida